2017
DOI: 10.1007/s10597-017-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Social Network Factors with Depression and Anxiety at Different Life Stages

Abstract: This study examines whether social network factors influence individual's depression and anxiety outcomes at different life stages. Data was drawn from the Household, Income and Labour Dynamics in Australia survey. Hierarchical regression modelling was applied to examine the effects within and across different life stages. The depression and anxiety measures were taken from the Kessler Psychological Distress Scale (K10) and the social network factors were taken from the self-completion questionnaire. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
2
23
0
1
Order By: Relevance
“…Findings from the current study are consistent with much of the literature on social isolation, in which it has been shown to have a well-established relationship with depression ( Challands et al, 2017 ; Cruwys et al, 2013 ; Levula et al, 2018 ; Santini et al, 2015 ; Taylor et al, 2018 ) and anxiety ( Lee and Robbins, 1998 , Liao et al, 2016 , Teo et al, 2013 ). However, the potential of psychological flexibility to serve as a limiting factor to isolation-related depression has not yet been explored.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Findings from the current study are consistent with much of the literature on social isolation, in which it has been shown to have a well-established relationship with depression ( Challands et al, 2017 ; Cruwys et al, 2013 ; Levula et al, 2018 ; Santini et al, 2015 ; Taylor et al, 2018 ) and anxiety ( Lee and Robbins, 1998 , Liao et al, 2016 , Teo et al, 2013 ). However, the potential of psychological flexibility to serve as a limiting factor to isolation-related depression has not yet been explored.…”
Section: Discussionsupporting
confidence: 88%
“…Social isolation has been defined as “an objective lack of interactions with others or the wider community” ( Leigh-Hunt et al, 2017 ) and is known to contribute to mental health problems, including general psychological distress ( Espinosa & Rudenstine, 2020 ), decreased well-being ( Liao & Weng, 2018 ), and depression ( Santini et al, 2015 ). It is a strong predictor of depression in older adults ( Challands et al, 2017 ; Cruwys et al, 2013 ; Taylor et al, 2018 ) and, in a large national Australian survey, it was found to predict depression across the lifespan ( Levula et al, 2018 ). In a systematic review, social isolation was found to be closely related to social anxiety disorder ( Teo et al, 2013 ).…”
mentioning
confidence: 99%
“…The etiology of anxiety as an illness includes a number of interacting biological, psychological, and social factors [ 49 ]. Individuals with better social networks are less likely to report anxiety symptoms [ 50 ]. Using class-based social groups may be able to improve college students’ positive psychology and promote a positive atmosphere to enhance strong-tie relationships [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out on the factors associated with psychological distress as measured by the K10 questionnaire. Studies on Australian samples have shown that psychological distress is associated with unemployment (Reavley et al, 2011), low income (Enticott et al, 2018; Reavley et al, 2011), low social capital (Phongsavan et al, 2006), low social connectedness and social support (Atkins et al, 2013; Levula et al, 2018); workplace characteristics (Considene et al, 2017); poor quality diet (Hodge et al, 2013; Nguyen et al, 2017), limitations on physical functioning (Atkins et al, 2013; Byles et al, 2014) and physical diseases (Byles et al, 2014). There may be limits on how much change treatment can produce where such risk factors are present and persisting.…”
Section: Discussionmentioning
confidence: 99%